Improved Value of Individual Prenatal Care for the Interdisciplinary Team - Ella Damiano; Regan Theiler (Journal of Pregnancy)
Objective. Innovative models of prenatal care are needed to improve pregnancy outcomes and lower the cost of care. We sought to increase the value of traditional prenatal care by using a new model (PodCare) featuring a standardized visit schedule and coordination of care within small interdisciplinary teams in an academic setting. Methods. Prenatal providers and clinic staff were divided into four “Pods”. Testing and counseling topics were assigned to visits based on gestational age. Interdisciplinary weekly Pod meetings provided coordination of care. A retrospective chart review was performed. The primary endpoints were the number of prenatal care visits and number of providers seen. Results. After PodCare implementation, more patients choose care with the low-risk physician team (42% compared to 26%). Study subjects included 85 women in 2013 and 165 women in 2014. The median number of visits decreased from 13 to 10 (p < 0.00004) and the median number of providers seen decreased from 7 to 5 (p < 0.0000008). Conclusion. PodCare increased the value of individual prenatal care by decreasing the number of visits, increasing continuity, and providing care coordination. The model provides a robust experience in interdisciplinary care. The PodCare model may be successful at other academic institutions.